Factors associated with the use of adjuvant radiation therapy in stage III melanoma - King, Amber L. O.; Lee, Victor; Yu, Beverly; Mirza, Fatima N.; Zogg, Cheryl K.; Yang, Daniel X.; Tran, Thuy; Leventhal, Jonathan; An, Yi (Frontiers in Oncology, 2023)
Objective: The role of radiation therapy (RT) in melanoma has historically been limited to palliative care, with surgery as the primary treatment modality. However, adjuvant RT can be a powerful tool in certain cases and its application in melanoma has been increasingly explored in recent years. The aim of this study is to explore national patterns of care and associations surrounding the use of adjuvant RT for stage III melanoma. Methods: The National Cancer Data Base (NCDB) was used to identify patients who were diagnosed with stage III melanoma between 2004 and 2014. Exclusion criteria included those with distant metastatic disease, in-situ histology, no confirmed positive nodes, palliative intent therapy, and dosing regimens inconsistent with National Comprehensive Cancer Network (NCCN) guidelines for adjuvant RT in melanoma. Patients treated with and without adjuvant RT were compared and factors associated with use of adjuvant RT were identified using multivariable logistic regression analyses. Results: A total of 7,758 cases of stage III melanoma were analyzed, of which 11.7% received adjuvant RT. The mean age of the overall cohort was 58.5 years, and the majority of patients were male (64.7%), white (96.6%), on private insurance (51.3%), and presented to a non-high-volume facility (90.3%). Multivariable regression analyses revealed that patients who present to the hospital in 2009-2014 as compared to 2004-2008 (odds ratio [OR] 1.61, 95% confidence interval [CI] 1.36-1.92), had 4 or more positive nodes (OR 4.30, 95% CI 3.67-5.04), and had microscopic residual tumor (OR 2.11, 95% CI 1.46-3.04) were more likely to receive adjuvant RT. Factors that were negatively associated with receiving adjuvant RT included female gender (OR 0.72, 95% CI 0.61-0.85) and median income of at least $63,000 (OR 0.66, 95% CI 0.52-0.83). Conclusions: This study demonstrates the rising use of RT for stage III melanoma in recent years and identifies demographic, social, clinical, and hospital-specific factors associated with patients receiving adjuvant RT. Further investigation is needed to explore disease benefits to improve guidance on the utilization of RT in melanoma.